In the army hands: violence and post war in guatemala (2007)
The fratricide war among sectors of the Mayan population in Guatemala (1962-1996) and permanent militarization has left sequels printed in the social tissue. In this research that includes the field work for Comisión de la Verdad, supported by the United Nations (1997-1998), I witnessed the destruction of confidence and solidarity ties, key components in the support of communal identity. My study intends to show how persistent militarization makes the most impoverished sectors from the rural population turns to the army as the guardian of their communities.